Reactivity of Factor VIII Inhibitors in a Micro ELISA for Factor VIII : CAg and in Solid Phase Immunoisolation of VIII : CAg - Nordfang, O; Ezban, M; Dinesen, B (Thrombosis and Haemostasis, 1985)
Factor VIII coagulant antigen (VIII : CAg) was measured in a sandwich-ELISA. Microplates were used as solid phase and peroxidase conjugated F(ab’)2 fragments of IgG isolated from inhibitor plasma was used as label without affinity purification. The capacity of the assay was high and the sensitivity for VIII : CAg was 0.002 U/ml. Using this assay it was possible to measure coagulation inactive VIII : CAg in samples from purification studies. Below 0.05 VIII : CAg U/ml these samples responded in parallel with standard plasma.Seven of 7 inhibitor antibodies tested were able to inhibit binding of peroxidase-conjugate in the VIII : CAg assay, and the inhibitory capacity correlated with coagulation inhibition as measured by the Bethesda method. Using the highest titered antibodies bound to a solid phase, VIII : CAg was isolated and identified in SDS-PAGE as a doublet with a molecular weight of 77-80 kD.
Keywords: Factor VIII : CAg; Solid phase immunoisolation; ELISA; Haemophilia A inhibitor antibodies